Space : From MAXXI's Collections of Art and Architecture. - Chiodi, Stefano; Dardi, Domitilla (Milan : Mondadori Electa, 2010)
Arienti, Stefano ; Assaël, Micol ; Ballo Charmet, Marina ; Beuys, Joseph ; Calzolari, Pier Paolo ; do Espírito Santo, Iran ; Esposito, Bruna ; Fabro, Luciano ; Fontana, Lucio ; Fulton, Hamish ; Gabellone, Giuseppe ; Gilbert & George ; Linke, Armin ; Losi, Claudia ; Nunzio ; Pascali, Pino ; Penone, Giuseppe ; Sterbak, Jana ; Warhol, Andy ; Zorio, Gilberto ; Rintala Eggertsson Architects ; West 8 ; Alterazioni Video ; Alÿs, Francis ; Avery, Charles ; Beecroft, Vanessa ; Brotherus, Elina ; Cabrita Reis, Pedro ; Cattelan, Maurizio ; Favaretto, Lara ; Garaicoa, Carlos ; Geers, Kendell ; Goetschalckx, Wannes ; Jaar, Alfredo ; Kapoor, Anish ; Kiefer, Anselm ; Merz, Mario ; Paci, Adrian ; Pietroiusti, Cesare ; Potrč, Marjetica ; Richter, Gerhard ; Smith, Kiki ; Steinbach, Haim ; Tirelli, Marco ; Trockel, Rosemarie ; Xhafa, Sislej ; Zen, Chen ; Estudio Teddy Cruz ; Lacaton & Vassal ; Cino Zucchi Architetti ; Anselmo, Giovanni ; Atelier Van Lieshout ; Boetti, Alighiero ; Favelli, Flavio ; Grimaldi, Massimo ; Kentridge, William ; Lucy + Jorge Orta ; Ruff, Thomas ; Vitone, Luca ; Weiner, Lawrence ; Khoury, Bernard ; Recetas Urbanas ; Airò, Mario ; Gnoli, Domenico ; Kabakov, Ilya + Kabakov, Emilia ; Khebrehzadeh, Avish ; LeWitt, Sol ; Mauri, Fabio ; Mochetti, Maurizio ; Ontani, Luigi ; Oursler, Tony ; Paolini, Giulio ; Pistoletto, Michelangelo ; Shonibare, Yinka ; Sikander, Shahzia ; Toderi, Grazia ; Vedovamazzei ; Vezzoli, Francesco ; Viola, Bill ; Diller Scofidio + Renfro ; HPNJ+ ; R&Sie(n) ; Studio Azzurro ; Bestiario ; Boredomresearch ; Bianco-Valente ; Crawford, David ; Heyrman, Hugo ; Les Liens Invisibles ; Loher, Katia ; Manetas, Miltos ; Vitiello, Stephen
Space. From Maxxi's Collections of Art and Architecture, MAXXI - Museo nazionale delle arti del XXI secolo, Rome, May 30, 2010 - January 23, 2011
kunstcatalogus